PENGGUNAAN GRAPHIC ORGANIZERS DALAM GERAKAN LITERASI SEKOLAH - Mutiara, Rika (Universitas Esa Unggul, 2020)
AbstractSchool literacy program has been conducted for several years in some junior high schools in Jakarta such as SMPN 220 Jakarta. However, there are some problems in the school. The school does not have enough teachers to assist the literacy program. The only activity in that program is reading. Sometimes, some students also tell their friends what they have read. In the other school, SMPN 191 Jakarta, school literacy program never exists. This community service program tried to help the schools planning and conducting an appropriate follow up activity of the reading activity. Graphic organizer is a tool that can be used to help the students understand the reading passages during the follow up activity. In using Graphic organizers, the students need to use their thinking skills to obtain several information related to the characters, events, and facts in the reading passages. The students become aware that reading is an activity to develop their cognitive by observing and digging up information. Ã‚Â Keywords: Literacy, graphic organizers, readingÃ‚Â AbstrakGerakan Literasi Sekolah (GLS) sudah berjalan selama beberapa tahun di beberapa SMP di Jakarta seperti SMPN 220 Jakarta.Walaupun begitu, masih ada kendala yang dihadapi oleh sekolah.Sekolah tidak memiliki cukup guru untuk memandu kegiatan tersebut.Kegiatan GLS yang ada saat ini hanya membaca saja.Kadang beberapa siswa diminta menyampaikan hasil bacaan.Di sekolah lainnya yaitu SMPN 191 Jakarta GLS belum pernah dilaksanakan.Kegiatan pengabdian masyarakat ini bertujuan untuk merancang dan mengaplikasikan tindak lanjut kegiatan membaca yang cocok untuk kondisi sekolah.Graphic organizers merupakan sarana yang bisa dimanfaatkan oleh siswa untuk mengolah informasi dalam bacaan.Penggunaannya tidak membutuhkan peran guru yang banyak.Siswa dilatih untuk teliti dalam mencermati informasi tokoh, peristiwa, dan fakta dalam bacaan.Siswa menjadi sadar bahwa membaca merupakan kegiatan untuk melatih diri berpikir melalui penggalian informasi yang mendalam.Ã‚Â Kata kunci: Literasi, graphic organizers, membaca